7학년 국어교과서의 어휘 통계조사 -노미숙, 김태철 교과서를 중심으로 - 김철수; Kim, Cheol-Su (한국콘텐츠학회 논문지, 14(4), 2014)
This paper studied the statistics such as the total number of syllables: the kinds of syllables: the frequency of syllables, the total number of eojeols, the kinds of eojeols(word phrases unique in Korean language), average length of eojeols and the frequency of eojeols in four different Korean textbooks for 7th-grade students. The results of the statistical survey are as follows: the number of syllables was 286,801; the kinds of Korean syllables were 1,350; the average frequency of syllables was 212.4; the number of eoieol was 109,393; the kinds of eoieol were 29,356; the average frequency of eojeol was 3.7; the average length of eojeols was 2.7 syllables, the longest one consist of 8 syllables. 본 연구는 중학교 7학년 국어교과서 4종에 나타나는 어휘들에 대한 통계(음절 개수, 음절 종류, 음절 출현 빈도, 어절 개수, 어절 종류, 어절 평균 길이, 어절 출현 빈도 등)를 조사하였다. 전체 한글 음절 개수는 286,801개, 한글 음절 종류는 1,350개, 음절 평균 출현빈도는 212.4회이다. 어절 개수는 109,393개, 어절 종류는 29,356개, 어절 평균 출현빈도는 3.7회이다. 평균 음절 길이는 2.7음절이며, 한글 어절 중 가장 긴 어절길이는 8이다.